2011
DOI: 10.4236/jct.2011.25095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4-Weekly vs 3-Weekly Gemcitabine as Adjuvant Chemotherapy Following Curative Resection for Biliary Tract Cancer: A Prospective Randomized Controlled Trial

Abstract: Background: Surgery for biliary tract cancer, including pancreatoduodenectomy and major hepatectomy, is too aggressive and does not allow postoperative gemcitabine to be administered by the usual dosage protocol. We hypothesized that the feasibility of 3-weekly protocol (days 1 and 8, every 3 weeks) of adjuvant gemcitabine therapy may be superior to the usual 4-weekly protocol (days 1, 8, and 15 every 4 weeks). Method: We compared the outcomes of 6 cycles of the 4-weekly protocol and 9 cycles of the 3-weekly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The RDI of gemcitabine was 77%, which was lower than that (86%) in the CONKO-001 study conducted in patients with pancreatic cancer [10], but was similar to that (75%) in a previous study conducted in patients with BTC [11]. Considering the final completion rate was 72% in our study, which was beyond the minimum tolerable rate of 66% defined before starting this study, we regarded this regimen as feasible in the adjuvant setting in patients who underwent curative resection with or without major hepatectomy.…”
Section: Discussionsupporting
confidence: 70%
“…The RDI of gemcitabine was 77%, which was lower than that (86%) in the CONKO-001 study conducted in patients with pancreatic cancer [10], but was similar to that (75%) in a previous study conducted in patients with BTC [11]. Considering the final completion rate was 72% in our study, which was beyond the minimum tolerable rate of 66% defined before starting this study, we regarded this regimen as feasible in the adjuvant setting in patients who underwent curative resection with or without major hepatectomy.…”
Section: Discussionsupporting
confidence: 70%
“…Tumoral and stromal SPARC expressions were examined for associations with major clinico‐pathological parameters—including previously reported prognostic factors, such as residual tumor , pathological lymph node metastasis , invasion into nervous system , vascular invasion ,histological diagnosis (e.g., poorly differentiated tubular adenocarcinoma) , and adjuvant therapy . No analyzed factor was related to tumoral positive reactivity for SPARC (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Their study enrolled 27 patients, and the authors concluded that the three-weekly protocol did not yield superior completion as the rate of adverse events or recurrence-free survival was similar to the four-week regimen. 45 The study by Kainuma et al assessed the feasibility and the efficacy of gemcitabine plus cisplatin (CDDP) for biliary tract cancer in the adjuvant setting. Gemcitabine at 1,000 and 25 mg/m 2 of CDDP on days 1 and 8 was repeated for every three weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Their study enrolled 27 patients, and the authors concluded that the three-weekly protocol did not yield superior completion as the rate of adverse events or recurrence-free survival was similar to the four-week regimen. 45…”
Section: Methodsmentioning
confidence: 99%